Rezension von: Herbert Berner (Hrsg.), Bodman Bd. 1 - Wunder, Gerd (Württembergisch Franken, 1978)
Bodman. Dorf, Kaiserpfalz, Adel. Band I. Hrsg. v. Herbert Berner. Sigmaringen: Thorbecke 1977. 352 S. Ill. DM 58,-.